رقابة القاضي الإداري على قرارات تجاوز السلطة الإدارية - أمینة صالح - یمینة بن ریة (جامعة محمد بوضياف المسيلة, 2018)
تعتبر القرارات الإدارية المشوبة بعيب تجاوز السلطة من أكثر الإشكاليات المطروحة أمام القضاء الإداري تعقيدا، فعيب تجاوز السلطة هو تحقيق الإدارة لهدف غير الذي منح لها من أجله تلك السلطة، ويظهر هذا العيب في صورتين هما مجانبة المصلحة العامة ومخالفة قاعدة تخصيص الأهداف، ومجاله يمس السلطة التقديرية عموما، إلا أنه لا يمنع من إمكانية وجود هذا العيب في مجال الإختصاص المقيد إضافة إلى أن حالاته ممثلة في عدم المشروعية الداخلية وعدم المشروعية الخارجية ثم أن إثبات عيب تجاوز السلطة أصلا يقع على المدعي، كما أن الوسائل التي يمكن اللجوء إليها في الإثبات تتمثل في وسائل مباشرة و أخرى غير مباشر، وختاما لذلك فإن الآثار المترتبة عن إثبات عيب تجاوز السلطة تتمثل في إلغاء القرار الإداري وتعويض عن الأضرار الناتجة عنه. The administrative decisions that are flawed by the excess of authority are one of the most complex problems facing the administrative jurisdiction. The defect of excess of authority is to achieve management for a purpose which it was not given authority. This defect is manifested in two forms; in the interest of the public and in the violation of allocation of objectives’ rule. Generally, it does not prevent that the defect could exist in restricted area of competence and their cases involve both internal illegality and external illegality. In addition, the prove of excess of authority is up to plaintiff and the means used to prove can be direct and indirect. In conclusion, the implications of proving the defect of the excess of authority consist in the invalidity of the administrative decision and compensation for the damage resulting from it.
Keywords: القاضي . القانون الإداري . القرارات . الرقابة . السلطة الإدارية